Problems of financing urban mobility resilience in Poland - Mercik, Anna (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The efficient functioning of transportation systems is subject to various types of disruptions and risks. Transportation systems are strongly affected by all kinds of local, regional, national, or global crises. The European Union’s transport policy indicates the need to build sustainable, intelligent, and resilient urban mobility systems based on public mass transit. The paradigm of resilience has gained particular importance in the context of the global crises of the last five years. Resilient urban mobility systems are intended to provide the ability to respond quickly to disruptions that occur, allowing urban organisms to achieve operational stability. Aim: The purpose of the study is to identify the main problems with financing the resilience of public mass transit systems in Polish cities. The specific aims are the identification of the factors determining the resilience of urban mobility systems and tools supporting it, measures of resilience and ways of financing it. The study sought to verify whether the mobility systems of Polish regional cities can be considered resilient from a financial point of view. Results: Financing urban public mass transport in Poland is based on two key sources of income: fees from ticket sales and payments (compensations) made by local governments. The economic and energy crisis contributed to a significant increase in the operating costs of public mass transportation providers. In this context, the key to building resilient public mass transport systems in urban areas is to make changes to existing models to ensure a stable PTA financing system.